2020
DOI: 10.1093/mnras/staa1378
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde orbits excess among observable interstellar objects

Abstract: In this work we investigate the orbital distribution of interstellar objects (ISOs), observable by the future wide-field National Science Foundation Vera C. Rubin Observatory (VRO). We generate synthetic population of ISOs and simulate their ephemerides over a period of 10 years, in order to select those which may be observed by the VRO, based on the nominal characteristics of this survey. We find that the population of the observable ISOs should be significantly biased in favor of retrograde objects. The inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous analyzes involving synthetic populations of ISOs (e.g. Engelhardt et al, 2017;Marčeta and Novaković, 2020) used a technique developed by Grav et al (2011). This technique is based on propagating an initially homogeneous and isotropic population over a sufficiently long time so that the resulting population represents a steady-state population altered by the effect of gravitational focusing in some predefined sphere surrounding the Sun.…”
Section: Dynamical Methods For Generating Synthetic Population Of Isosmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous analyzes involving synthetic populations of ISOs (e.g. Engelhardt et al, 2017;Marčeta and Novaković, 2020) used a technique developed by Grav et al (2011). This technique is based on propagating an initially homogeneous and isotropic population over a sufficiently long time so that the resulting population represents a steady-state population altered by the effect of gravitational focusing in some predefined sphere surrounding the Sun.…”
Section: Dynamical Methods For Generating Synthetic Population Of Isosmentioning
confidence: 99%
“…thetic populations within such large heliocentric spheres. For example, Engelhardt et al (2017) and Marčeta and Novaković (2020) analysed synthetic populations inside model spheres with radii 50 au and 100 au, respectively. The reason for this was that objects within these spheres are capable of reaching heliocentric distances at which they could be detected by the LSST survey during the defined nominal duration of this survey of 10 years (LSST Science Collaboration et al, 2017).…”
Section: Comparison Of Probabilistic and Dynamical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular example shown in this work showed that the probability of such an event is significant. Moreover, the latest simulations of Marčeta & Novaković (2020) indicate that there are a very large number of retrograde orbits among interstellar objects. This is a serious clue to further exploration in this area.…”
Section: Introductionmentioning
confidence: 99%